Shielding the Gut: Ghrelin and Ferrostatin-1’s Protective Role Against Sepsis-Induced Intestinal Ferroptosis - Qiliang Hou; Zhimin Dou; Lei Zhu; Bin Li (Biomedicines)
Objective: This study investigates the therapeutic efficacy of ghrelin in alleviating sepsis-induced intestinal damage, focusing on its potential to inhibit ferroptosis and protect intestinal barrier integrity. Methods: This study evaluates the therapeutic efficacy of intraperitoneal ghrelin (80 μg/kg) and Ferrostatin-1 (5 mg/kg) using a cecal ligation and puncture (CLP) model in C57BL/6 mice to determine their potential in alleviating sepsis-induced intestinal damage. The investigation focuses on the impacts of ghrelin and Ferrostatin-1 on bacterial load, intestinal morphology, systemic inflammation, oxidative stress, and ferroptosis markers. Our comprehensive methodology encompasses histopathological evaluations, cytokine profiling, oxidative stress assays, and detailed analyses of ferroptosis indicators to thoroughly assess the interventions’ efficacy. Results: Treatment with ghrelin significantly reduced bacterial proliferation, mitigated intestinal damage, and decreased systemic inflammation. Comparable outcomes were observed with Fer-1 treatment. Both interventions restored intestinal barrier functions, modulated inflammatory responses, and attenuated oxidative stress, indicating a suppression of the ferroptosis pathway. Conclusion: Ghrelin exhibits a protective role in sepsis-induced intestinal injury, likely through the inhibition of ferroptosis. This mechanism underscores ghrelin’s therapeutic potential in sepsis management, suggesting avenues for further clinical exploration.